Representações de agentes socioeducadores/as : um estudo baseado na análise crítica do discurso - Lima, Janice Raquel de (2016)
In this research, through the category of representational meaning of the discourse, I propose the identification and analysis of the linguistic-discursive representations of four social-educational agents about their profession and continuing education and social reintegration of adolescents in social vulnerability. Furthermore, I analyze a compliance of such representations with the guidelines of care to the adolescent deprived of freedom recommended by the Child and Adolescent Statute ECA (1990) and by the National System of Social Educational Services (SINASE) (2012). Such agents perform their duties in the Socio Educational Centers (Pomeri Complex) of Cuiabá, linked to the Department of Justice and Human Rights of the State of Mato Grosso (SEJUDH). I am also interested in understanding the work routine of the socio-educational agents, from a historical, political, social and ideological point of view. Thus, I sought to give them voice, through semi-structured interviews and field observations. These agents are responsible for the social education of adolescents in a situation of social vulnerability, who are under legal custody. The adolescents fulfill social-educational measures of deprivation of freedom, as foreseen in ECA, Law No. 8.069, of June 13, 1990, and SINASE (2012.). The investigation of the agents’ representations in relation to their profession; the relevance of the continuing education and social reintegration of adolescents deprived of freedom aims to improve socio-educational actions. Getting to know these agents is fundamental to understand whether, in fact, the Pomeri complex offers conditions or not to reintegrate adolescents in social risk. It is a study based on the methodology of the Critical Discourse Analysis (CDA) (FAIRCLOUGH, 2001, 2003a), which considers the use of language a form of social practice and not a merely individual or situational activity. The critical analytical method of discourse aims at proposing changes in the relations of power and oppression present in the social structures. It is also based on Critical Realism (BHASKAR, 1998), for whom social reality is understood as the articulation of social structures and human action. This research is also guided by the theoretical foundations of the Systemic-Functional Linguistics by Halliday (1994), according to which any and all use of the linguistic system is functional to the needs of social coexistence. Based on the aforementioned theoretical foundation, I have as specific objectives: (1) To identify and analyze the socio-educational agents’ representations in relation to their profession, continuing education and reintegration of the adolescents deprived of freedom, and how this is materialized in the texts; (2) to identify and analyze, through linguistic materiality, whether the agents have some humanistic education that can contribute or not, to a more harmonic relation with the adolescents; (3) whether the agents believe in the reintegration of these adolescents. The research methodology is qualitative. The results of the analyses clarify the specificities of the profession of socio-educational agent and the need and the importance of investments in the human/professional continuing education for these professionals. Getting to know their work context was fundamental to understand if the Pomeri Complex is a place of emancipation, or oppression, which may or may not provide social reintegration of adolescents deprived of freedom.